2022
DOI: 10.1155/2022/4603638
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Soil-Transmitted Helminth Infections among Schoolchildren around Lake Tana, Northwest Ethiopia

Abstract: Background. Soil-transmitted helminths (STHs) are among the most common neglected tropical diseases widely distributed in tropical countries with poor socioeconomic development. Ascaris lumbricoides, Trichuris trichiura, and hookworm are the three major STHs. This study aimed to determine the prevalence of STHs and associated risk factors among schoolchildren in selected primary schools around Lake Tana, Northwestern Ethiopia. Methods. A school-based cross-sectional study was conducted from February to May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, some publsihed, studies in Northern and Souhern Ethiopia have identi ed hookworm as the dominant infection in speci c sites, with Trichuris beinng most common in the SouthWest of Ethiopia. These variations are probably related to the variations in climatic conditions such astemprature and humidity that in unce the survival of infective larvae and helminth eggs (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…However, some publsihed, studies in Northern and Souhern Ethiopia have identi ed hookworm as the dominant infection in speci c sites, with Trichuris beinng most common in the SouthWest of Ethiopia. These variations are probably related to the variations in climatic conditions such astemprature and humidity that in unce the survival of infective larvae and helminth eggs (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…[19] Untrimmed fingers, shoewearing habits, playing on contaminated soil, and lack of knowledge about the route of transmission. [20] Poor environmental sanitation, unsafe human waste disposal systems, poor personal hygiene, frequent outdoor exposures, a lack of a safe water supply, and the low socioeconomic status of the country are considered risk factors for STH infections. [21]…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews have reported an association between hygiene-related behavioral risk factors and the transmission of STH infections. For example, among schoolchildren, the following meta-analytic estimates have been reported: poor handwashing (OR 1.55, 95% CI 0.61 to 3.92, p < 0.001), open defecation (OR 5.20, 95% CI 1.35 to 20.16, p < 0.001), untrimmed fingernails (OR 3.21, 95% CI 1.57 to 6.55, p = 0.001), and not wearing footwear (OR 29.5, 95% CI 6.59 to 132.55, p < 0.001) [7,8]. Other adverse risk factors discussed in the literature include nail biting, soil eating, eating raw unwashed vegetables, swimming in water bodies, and close contact with animals [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%